The Effect of Manipulative Learning Media on Students' Mathematical Concept Understanding Ability in SMP Swasta Mawar - Erlis Chrisanti Lase; Yulisman Zega (Edumaspul: Jurnal Pendidikan, 2023)
One of the problems in learning mathematics at SMP Swasta Bunga Mawar is that students' ability to understand mathematical concepts is still lacking. The aim of this research is to determine the effect of manipulative learning media on students' ability to understand mathematical concepts at SMP Swasta Bunga Mawar. This type of research is quantitative research using a quasi-experimental method (quasi experimental design). This research was carried out at SMP Swasta Bunga Mawar, with the research population being class IX for the 2023/2024 academic year. The research sample was taken by random sampling, the classes that were the research sample were class IX-B as the experimental class, and class IX-C as the control class. The instrument used in this research is a written test in the form of a description test and consists of an initial test and a final test. The research results showed that the average initial test score obtained by the experimental class was 53.75 (poor category) and the control class was 40.89 (poor category). while the average final test score for the ability to understand mathematical concepts obtained by the experimental class was 71.60 (good category) and the control class was 55.18 (fair category). From the research results obtained based on hypothesis testing, namely th = 3.994 and tt= 1.701. Because th = 3.994> tt= 1,701, then reject H0 and accept Ha which means "There is an influence of manipulative learning media on ability students' understanding of mathematical concepts at SMP Swasta Bunga Mawar”.